The impact of Istanbul on the construction of Albania’s religious and cultural coexistence - Shehu, Fatmir Mehdi (Instanbul University, 2010)
When Istanbul (then Constantinople) was ruled by the Byzantine Christian governors, it witnessed many religious, economic, political, cultural, and social problems, which had created an intolerant environment dominating all aspects of Istanbul’s day-to-day interactions. The religious and cultural activities of Istanbul’s community were very exclusivistic in nature. Openness with others in and out Istanbul was not encouraged; rather it was forbidden. However, Istanbul’s intolerant climate was changed to tolerant inter-religious and cultural coexistence during the Ottoman Muslims’ administration. In this sense, Istanbul, not only became the capital city of Ottoman Caliphate, but it became a very important centre of religious and cultural pluralism built on the premises of mutual respect and tolerant coexistence, which helped its community, as well as the communities under its governance, to progress in all aspects of life. This paper has attempted to study: (i) an introduction about Albania and Albanians; (ii) the new paradigm shift of religious and cultural pluralism that was introduced by Ottoman Muslims to Istanbul; (iii) the impact of Istanbul on the construction of Albania’s religious and cultural coexistence, which was made a reality after the Ottoman Muslims stepped on the Albanian shores. This paper has reached at the conclusion that Istanbul’s metropolitan community and tolerant administration had a great impact on the foundation of Albania’s society.